Resistencia, resistencias - Klein, Jean-Pierre (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
The concept of resistance is reviewed, initially from its political sense and later in its psychological sense in relation to change. The article values the paper of the art therapy and the function of the artists in that context, in relation to the resistance and the treatment of the differences.